Cornelius Nepos, Life of Hannibal Latin Text, Notes, Maps, Illustrations and Vocabulary - Mulligan, Bret (Dickinson College Commentaries, 2015)
"Trebia. Trasimene. Cannae. With three stunning victories, Hannibal humbled Rome and nearly shattered its empire. Even today Hannibal's brilliant, if ultimately unsuccessful, campaign against Rome during the Second Punic War (218-202 BC) make him one of history's most celebrated military leaders. This biography by Cornelius Nepos (c. 100-27 BC) sketches Hannibal's life from the time he began traveling with his father's army as a young boy, through his sixteen-year invasion of Italy and his tumultuous political career in Carthage, to his perilous exile and eventual suicide in the East. As Rome completed its bloody transition from dysfunctional republic to stable monarchy, Nepos labored to complete an innovative and influential collection of concise biographies. Putting aside the detailed, chronological accounts of military campaigns and political machinations that characterized most writing about history, Nepos surveyed Roman and Greek history for distinguished men who excelled in a range of prestigious occupations. In the exploits and achievements of these illustrious men, Nepos hoped that his readers would find models for the honorable conduct of their own lives. Although most of Nepos' works have been lost, we are fortunate to have his biography of Hannibal. Nepos offers a surprisingly balanced portrayal of a man that most Roman authors vilified as the most monstrous foe that Rome had ever faced. Nepos' straightforward style and his preference for common vocabulary make Life of Hannibal accessible for those who are just beginning to read continuous Latin prose, while the historical interest of the subject make it compelling for readers of every ability."